Protection of wetlands as a strategy for reducing the spread of avian influenza from migratory waterfowl - Wu, Tong (Ambio, 2019)
Highly pathogenic avian influenza (HPAI) H5N1 has led to the death or destruction of millions of domesticated and wild birds and caused hundreds of human deaths worldwide. As with other HPAIs, H5N1 outbreaks among poultry have generally been caused by contact with infected migratory waterfowl at the interface of wildlands and human-dominated landscapes. Using a case–control epidemiological approach, we analyzed the relation between habitat protection and H5N1 outbreaks in China from 2004 to 2017. We found that while proximity to unprotected waterfowl habitats and rice paddy generally increased outbreak risk, proximity to the most highly protected habitats (e.g., Ramsar-designated lakes and wetlands) had the opposite effect. Protection likely involves two mechanisms: the separation of wild waterfowl and poultry populations and the diversion of wild waterfowl from human-dominated landscapes toward protected natural habitats. Wetland protection could therefore be an effective means to control avian influenza while also contributing to avian conservation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13280-019-01238-2) contains supplementary material, which is available to authorized users.